2022
DOI: 10.1186/s12893-022-01735-4
|View full text |Cite
|
Sign up to set email alerts
|

Development of a nomogram to predict surgical site infection after closed comminuted calcaneal fracture

Abstract: Background Compared with open comminuted calcaneal fractures, less emphasis is placed on postoperative surgical site infection (SSI) of closed comminuted calcaneal fractures. This study aimed to identify the risk factors associated with SSI and build a nomogram model to visualize the risk factors for postoperative SSI. Methods We retrospectively collected patients with closed comminuted calcaneal fractures from the Second Affiliated Hospital of Wen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Studies have showed that risk factors for venous thrombosis following spinal surgery are associated with high age, female, spinal fusion, big volume blood loss patients, operation time, and hypertension, diabetes, and walking issue. A series of risk prediction models for deep venous thrombosis after surgery for patients with spinal surgery and fracture (Cheng et al, 2022;Hu et al, 2022;Yan et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have showed that risk factors for venous thrombosis following spinal surgery are associated with high age, female, spinal fusion, big volume blood loss patients, operation time, and hypertension, diabetes, and walking issue. A series of risk prediction models for deep venous thrombosis after surgery for patients with spinal surgery and fracture (Cheng et al, 2022;Hu et al, 2022;Yan et al, 2022).…”
Section: Introductionmentioning
confidence: 99%